2019
DOI: 10.3847/1538-4357/ab4f6f
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Extreme Ultraviolet Radiation Environment of Exoplanets around Low-mass Stars: GJ 832, GJ 176, and GJ 436

Abstract: Correct estimates of stellar extreme ultraviolet (EUV; 100 -1170Å) flux are important for studying the photochemistry and stability of exoplanet atmospheres, as EUV radiation ionizes hydrogen and contributes to the heating, expansion, and potential escape of a planet's upper atmosphere. Contamination from interstellar hydrogen makes observing EUV emission from M stars particularly difficult, and impossible past 100 pc, and necessitates other means to predict the flux in this wavelength regime. We present EUV -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 119 publications
3
49
2
Order By: Relevance
“…observation of fluorescent H 2 originating from the lowerexcitation v″=1 state and the absence of fluorescent H 2 originating from the higher-excitation v″=2 as evidence for a low-temperature (T(H 2 )1500 K) molecular component to the atmosphere of Barnard's Star. The physical location within the stellar atmosphere of this cool component is not clear and may provide interesting constraints on future models of M dwarf atmospheres (Fontenla et al 2016;Peacock et al 2019). While 1500K is cooler than the 2600 K chromospheric temperature minimum estimated from the M1.5V model atmosphere of Fontenla et al (2016), it is consistent with the chromospheric minimum found in the M8V model atmosphere calculated by Peacock et al (2019).…”
Section: Active Fuv Flaring On Barnard's Starmentioning
confidence: 99%
See 1 more Smart Citation
“…observation of fluorescent H 2 originating from the lowerexcitation v″=1 state and the absence of fluorescent H 2 originating from the higher-excitation v″=2 as evidence for a low-temperature (T(H 2 )1500 K) molecular component to the atmosphere of Barnard's Star. The physical location within the stellar atmosphere of this cool component is not clear and may provide interesting constraints on future models of M dwarf atmospheres (Fontenla et al 2016;Peacock et al 2019). While 1500K is cooler than the 2600 K chromospheric temperature minimum estimated from the M1.5V model atmosphere of Fontenla et al (2016), it is consistent with the chromospheric minimum found in the M8V model atmosphere calculated by Peacock et al (2019).…”
Section: Active Fuv Flaring On Barnard's Starmentioning
confidence: 99%
“…The physical location within the stellar atmosphere of this cool component is not clear and may provide interesting constraints on future models of M dwarf atmospheres (Fontenla et al 2016;Peacock et al 2019). While 1500K is cooler than the 2600 K chromospheric temperature minimum estimated from the M1.5V model atmosphere of Fontenla et al (2016), it is consistent with the chromospheric minimum found in the M8V model atmosphere calculated by Peacock et al (2019).…”
Section: Active Fuv Flaring On Barnard's Starmentioning
confidence: 99%
“…TOI-1231ʼs fundamental stellar properties are very similar to GJ 436ʼs, and our PFS spectra indicate that TOI-1231ʼs log 10 ¢ = -R 5.06 HK is nearly equivalent to GJ 436ʼs (−5.09;Boro Saikia et al 2018), indicating the same level of magnetic activity. Because ¢ R HK is known to correlate well with UV emission (Youngblood et al 2017), we assume GJ 436ʼs synthetic X-ray and UV spectrum from Peacock et al (2019) as a proxy for TOI-1231ʼs. The integrated flux from 100 to 912 Å at 0.13 au is 172 erg cm −2 s −1 but could be as low as ∼53 erg cm −2 s −1 , according to the estimates from the MUSCLES Treasury Survey (France et al 2016;Loyd et al 2016;Youngblood et al 2016) based on Linsky et al (2014).…”
Section: Probing Atmospheric Escapementioning
confidence: 99%
“…See García Muñoz et al (2020) and references within for more details about the method. The model simulations shown in Figure 8 are specific to the stellar spectrum from Peacock et al (2019) and assume supersonic conditions at r/R p ∼ 10. We take the stellar spectrum in its original format, 64 correcting only for orbital distance.…”
Section: Probing Atmospheric Escapementioning
confidence: 99%
“…This means that we obtain realistic F EUV /F bol within our models despite this inadequacy. For a recent detailed analysis of a synthetic EUV PHOENIX spectrum computed for the inactive M dwarf Ross 905, we refer to the study by Peacock et al (2019).…”
Section: Model Euv Flux and Its Effect On The He I Ir Linementioning
confidence: 99%